PENGARUH PARTISIPASI PENGANGGARAN DAN EVALUASI ANGGARAN TERHADAP KINERJA APARATUR PEMERINTAH (Studi Empiris di Lingkup Pemerintah Propinsi Maluku) - sososutiksno, Christina; Basuki, Ferry Hendro (Jurnal Akuntansi, 2021)
This study aims to analyze the influence of Budgetary Participation and Budget Evaluation on the Performance of Government Apparatuses in the Maluku provincial government. The population in this study is the State Civil Apparatus (ASN) in the Maluku Provincial Government which consists of 47 Regional Apparatus Organizations (OPD). The sample consisted of the Head of OPD, Head of Division, Head of Sub- Division, and Staff who were involved in preparing the budget. The data collection method used is a questionnaire. The number of questionnaires distributed was 150 copies (100%) and 132 copies (88%). The analytical technique used in this research is multiple linear regression analysis. The data is processed using the SPSS 20 application. The results of the analysis carried out show that the budgetary participation variable has a positive and significant effect on the performance of government officials with the t-statistics test value of hypothesis one with a coefficient value: 0.19 and a probability value: 0.02. Furthermore, the results of the second hypothesis t statistics test with a coefficient value: 0.13 and a probability value: 0.55, this shows that there is no influence between the budget evaluation variable on the performance variable of the Maluku Provincial Government apparatus.